The limits to employee involvement? Employee participation without HRM in a small not-for-profit organisation. Issue 2 (16th July 2020) - Philip, Karen; Arrowsmith, Jim
Abstract : Purpose: The strategic human resource management (HRM) literature emphasises the importance of employee involvement and participation for outcomes such as job satisfaction, employee retention and organisational performance. Situational factors identified as conducive to employee participation in decision-making include small size, via less hierarchical, proximate and informal workplace relations. Ownership and mission are also important, with not-for-profit (NFP) organisations generally having more collectivist, commitment-based cultures that support open decision-making. However, such organisations often have weak HRM policies and practices. This paper examines the process and outcomes of employee participation in a small NFP through in-depth case study research. Design/methodology/approach: Single case study utilising longitudinal participant observation, interviews, reflective diary, documentary analysis. Findings: Operating as a collective, the organisation was bound by time and capacity limitations in its ability to plan strategically or even to make routine decisions. Basic HR policies and practices in areas such as staff recruitment and performance management were sub-standard or unobserved. Consequences included poor management, inconsistent training, staff burnout, high labour turnover and sub-optimal performance. The results suggest that weak managerial coordination and the absence of a dedicated HR function subvert effective people management. In such circumstances, strong forms of employee participation fail to deliver anticipated equity and efficiency outcomes. Research limitations/implications: Single case study. Practical implications: Small organisations need HR policies and dedicated support to ensure that employee involvement and participation are effective. Originality/value: The findings demonstrate how employee involvement and participation can be subverted by inadequate HR processes, adding qualitative evidence to support theories of HR "bundling" in high-involvement work practices. The research also contributes to the neglected area of HRM in small NFPs.